Role of pore structure in the percolation and storage capacities of deeply buried sandstone reservoirs: A case study of the Junggar Basin, China. (March 2020) - Qiao, Juncheng; Zeng, Jianhui; Jiang, Shu; Ma, Yong; Feng, Sen; Xie, Huafeng; Wang, Yanu; Hu, Huiting
Abstract: Deeply buried sandstone reservoirs are characterized by their wide pore-throat distributions and varied storage and percolation capacities. An integrated analysis comprising casting thin section, scanning electron microscopy, X-ray computed tomography (micro-CT), high-pressure mercury intrusion (HPMI), and constant-rate mercury intrusion (CRMI) is performed on thirteen samples from the Jurassic Sangonghe Formation in the Junggar Basin to investigate the pore structures and their influence on the storage and percolation capacities. HPMI, CRMI, and micro-CT are combined to determine the full-range pore size distributions (FPSDs), which have multimodal distributions between 2.77 nm and 500 μm with three broad peaks. The right peak, ranging from 100 to 500 μm, is associated with residual and dissolution intergranular pores. The middle peak is mainly composed of dissolution intergranular and intragranular pores with radii between 10 and 100 μm. The left peak exhibited fluctuations and is characterized by dissolution intragranular and intercrystalline pores with radii of 37 nm–10 μm. According to the pore types, sizes, and proportions in the FPSD, the pores are classified as intercrystalline nanopores (<1 μm), intragranular micro-small pores (1–10 μm), mixed intergranular and intragranular mesopores (10–100 μm), and intergranular macropores (>100 μm). A storage capacity evaluation combining the classifications and FPSD indicates that the macropores and nanopores primarily contribute to porosity, albeit with contrasting influences on the storage capacity. The contents of macropores determine the storage capacity of a deeply buried sandstone reservoir, while the negative effects of nanopores become predominant with decreasing porosity. A percolation capacity evaluation on the basis of CRMI results suggests that the permeability contribution is dominated by nanopores in tight sandstone, controlled by micro-small pores in low-permeability sandstone, and dominated by mesopores in conventional sandstone. Mesopores always play a favorable role in percolation. However, the negative impacts of nanopores should be considered in low-permeability and tight sandstone. Micro-small pores have a negative influence on the permeability of conventional sandstone, but are favorable for the fluid percolation of most low-permeability and tight sandstone reservoirs. A new empirical equation indicates that r10 of the FPSD is the suitable as the proper pore-throat radius for the permeability estimation of deeply buried sandstone reservoirs. Highlights: HPMI, CRMI and Micro-CT are combined to obtain the full-range pore size distribution. A new pore classification is proposed for deeply buried sandstone reservoirs. Nanopore and macropore are considered main controlling factors for storage capacity. Nanopore, micro-small pore and mesopore serve as main throats for fluid percolation. A permeability estimation model is proposed by determining proper pore-throat radius.